Employee Performance Analysis Based on Human Resources Management Practices in Private Hospital in Surakarta - Rini Handayani; Kasidin Kasidin (Media Ekonomi dan Manajemen, 2022)
Human resource management (HRM) is the foundation to face business competition. Organizational strategies related to HRM create satisfaction among employees so that employees perform well and can create a competitive advantage for their organization. The need for human resources in the hospital industry has developed along with the availability of hospitals reaching 2813 hospitals in Indonesia. This of course requires superior human resources performance. HRM practices are expected to drive human resources performance and achieve a competitive advantage in the hospital industry. This study will examine the effect of HRM practices, namely training, performance appraisal, and compensation systems on employee performance. Furthermore, this study will also examine the role of job satisfaction to mediate HRM practices on employee performance. The study was conducted in a private hospital in the Surakarta area with a sample of 120 respondents. Convenience sampling technique as a sampling method used to collect samples using a questionnaire. SmartPLS is used to analyze research data. The results showed that there was a significant positive effect on HRM Practices (training, performance appraisal, compensation system) on employee performance. However, job satisfaction only mediates the effect of performance appraisal and compensation system on employee performance, while job satisfaction does not play a role in mediating the effect of training on employee performance..